Peran Empati dalam Pengajaran Sejarah: Tinjauan Literatur - Aderoben, Andromeda; Darmawan, Wawan; Saripudin, Didin (Jayapangus Press, 2024)
The role of history learning in reducing the empathy crisis is to ground historical empathy. However, teaching and research on historical empathy has not been very massive because in Indonesia the concept of historical empathy is relatively new and not much empirical data has been adopted by academics. This research aims to map the concept and teaching of historical empathy in history learning. This research uses qualitative research with a literature review method, that is: first, identifying the problem statement; second, identifying the problem statement; and third, identifying the problem statement: first, identifying the problem statement; second, identifying relevant research; third, selecting research; fourth, mapping data; and fifth, compiling, summarizing, and reporting results. The results of this study include the definition of historical empathy from various experts presented with a continuum line that is preceded by historical debates and followed by elements of historical empathy from the cognitive and affective domains and a combination of both, as well as historical empathy didactics which include: learning models that have been developed; suitable learning materials or themes; learning reflection or evaluation activities; and the level of achievement of historical empathy for students. The implication of this study is as a literature option for further researchers and as a reference material for history teachers in designing lessons that want to develop historical empathy skills in order to strengthen the character of the “Profil Pelajar Pancasila